First Term Support for International Graduate Students Attending Small Colleges and Universities - Shane, Mary Jo; Carson, Loredana; Macri, Diana Gloria (Journal of International Students, 2020)
The recruitment and retention of international students in academic institutions in the United States has become more complicated and more competitive than ever before given the current political climate and governmental policies. This article discusses some of the specific challenges international students face and what a small- to medium-sized private university has put in place to attract these students and to better prepare them for graduate level management courses starting their first term. This example introduces an 11-week foundations course along with additional resources designed to provide knowledge, instruction, and practice in skills and behaviors crucial for academic success within the United States.